Case Report: Anlotinib Therapy in a Patient With Recurrent and Metastatic RAIR-DTC Harboring Coexistent TERT Promoter and BRAFV600E Mutations - Su, Yanjun; Cheng, Shaohao; Qian, Jun; Zhang, Min; Li, Tuanli; Zhang, Ying; Diao, Chang; Zhang, Ling; Cheng, Ruochuan (Frontiers in Oncology, 2021)
We describe a case of recurrent and metastatic radioactive iodine-refractory differentiated thyroid cancer (RAIR-DTC) treated with anlotinib in this report. The patient was randomized to placebo initially, after disease progressed at C8, the patient was referred to the open label therapy of anlotinib, 12mg p.o. daily with a 2-week on/1-week off regimen. Partial response was achieved at C2 with anlotinib treatment. To date, over 37 months of progression-free survival (PFS) has been achieved. Adverse effects were tolerable and manageable in this patient. Molecular characterization revealed coexistent C228T mutation of TERT promoter and BRAFV600E mutations. Favorable clinical outcome in this patient suggests that anlotinib might provide a novel effective therapeutic option for patients with RAIR-DTC. TERT and BRAFV600E mutations may represent as biomarker for predicting salutary effects of anlotinib.